Laser lift-off scribing of the CZTSe thin-film solar cells at different pulse durations. (1st July 2017) - Markauskas, Edgaras; Gečys, Paulius; Repins, Ingrid; Beall, Carolyn; Račiukaitis, Gediminas
Highlights: CZTSe layer lift-off validation was made covering ps and sub-ps pulse durations. Fast CZTSe expansion and the reduction of the adhesion forced layer spallation. Sub-ps pulses induced more significant CZTSe layer electrical degradation. Highest simulated module efficiencies were obtained for 10 ps pulse P3 scribing. Abstract: The transition to fully sized solar modules requires additional three-step laser structuring processes to preserve small-scale cell efficiencies over the large areas. The adjacent cell isolation (the P3 scribe) was found to be the most sensitive process in the case of laser induced damage. The laser induced layer lift-off mechanism seems to be a very attractive process for the P3 patterning, since almost all the laser affected material is removed by mechanical spallation. However, a laser induced layer spallation behavior together with scribe electrical validation under the different laser pulse durations was not investigated extensively in the past. Therefore, we report our novel results on the P2 and P3 laser lift-off processing of the Cu2 ZnSn(S, Se4 ) (CZTSe) thin-film solar cells covering the pulse duration range from 300 fs to 60 ps. Shorter sub-ps pulses enabled us to process smaller P2 and P3 craters, although the lift-off threshold fluences were higher compared to the longer ps pulses. In the case of the layer lift-off, the laser radiation had to penetrate through the layer stack down to the CZTSe/Mo interface. At shorter sub-ps pulses, the nonlinear effects triggered absorption of the laser radiation in the bulk of the material, resulting in increased damage of the CZTSe layer. The Raman measurements confirmed the CZTSe surface stoichiometry changes for shorter pulses. Furthermore, shorter pulses induced higher electrical conductivity of a scribe, resulting in lower photo-electrical efficiency during the mini-module simulation. In the case of the P3 lift-off scribing, the 10 ps pulses were more favorable than shorter femtosecond pulses.